Association of the polymorphisms of MMP-9 and TIMP-3 genes with thoracic aortic dissection in Chinese Han population - Wang, Xiao-long (Acta Pharmacol Sin, 2014)
AIM: Thoracic aortic dissection (TAD) is the most common life-threatening disorder, and a shifted balance of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) is involved in TAD pathogenesis. The aim of this study was to evaluate the association of 4 single-nucleotide polymorphisms (SNPs) in MMP-9 and TIMP-3 genes with TAD risk in Chinese Han population. METHODS: A total of 206 Chinese patients with TAD and 180 controls were included in this study. Four SNPs (rs3918249, rs2274756, rs9609643 and rs8136803) were genotyped using high-throughput MALDI-TOF mass spectrometry. Allele and genotype association analyses were conducted using PLINK. RESULTS: All the 4 SNPs resulted in Hardy-Weinberg equilibrium in patients and controls. The G allele frequency for the MMP-9 SNP rs2274756 was significantly higher in female TAD patients than in female controls (P=0.0099). Moreover, after adjusting for traditional cardiovascular risk factors (sex, age, hypertension, dyslipidemia, diabetes and smoking habit), the rs2274756 polymorphism (odds ratio: 0.30; 95% confidence interval: 0.11 to 0.79, P=0.015) resulted in an independent susceptibility factor for TAD in females. No associations were found between the other SNPs and TAD. CONCLUSION: The results provide strong evidence for an association between MMP-9 SNP rs2274756 and female TAD risk in Chinese Han population.